UPAYA MENINGKATKAN HASIL BELAJAR MATEMATIKA MELALUI PENDEKATAN MATEMATIKA REALISTIK BERBANTUAN MEDIA LEGO PADA SISWA KELAS III-B UPT. SD NEGERI 01 LIMO KAUM - Rukmini Rukmini (Ensiklopedia of Journal, 2021)
This study aims to improve student learning outcomes as well as to achieve the target criteria for completeness in learning mathematics on simple fractions material in class III-B UPT students. SD Negeri 01 Limo Kaum. In this study, learning was carried out by applying a realistic mathematical approach using contextual problems assisted by lego media. This type of research uses Classroom Action Research (PTK) with the steps of planning, implementing, observing, and reflecting which is carried out in two cycles. The data collection techniques used were tests, observation and documentation. The subjects of this study were class III-B UPT. SD Negeri 01 Limo Kaum with 22 students. The results of the study can be seen that the complete cycle I was 16 students or 72.73% and 6 students or 27.27% who had not completed the class with a class average of 77.27. In Cycle II, there were 20 students or 90.91% who had not completed and 2 students who had not completed it or 9.09% with a class average of 87.27. This shows that a realistic mathematical approach assisted by lego media can be said to improve learning outcomes of fraction material in class III-B UPT students. SD Negeri 01 Limo Kaum.